2019
DOI: 10.1039/c9tx00083f
|View full text |Cite
|
Sign up to set email alerts
|

Association of smoking with coronary artery disease in Nepalese populations: a case control study

Abstract: There are well-known traditional risk factors for coronary artery disease (CAD). Among them, smoking is one of the most prominent and modifiable risk factors. This study aims to determine the magnitude of smoking as a risk factor for CAD in the Nepalese population. A hospital-based age- and sex-matched case–control study was carried out with a total of 612 respondents. Bivariate analysis showed that the risk of developing CAD in ex-smokers and current smokers was higher (odds ratio (OR): 1.81 (confidence inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
1
0
0
Order By: Relevance
“…The results of a study in China reported that smoking can increase the risk of all subtypes of CVD [16]. Another study conducted in Nepal also stated that smoking is known to increase the risk of heart artery disease in people in Nepal [17]. This result is in line with the study from Savia et al, (2013) which stated that there is a relationship between smoking and the risk of CVD.…”
Section: Discussionsupporting
confidence: 71%
“…The results of a study in China reported that smoking can increase the risk of all subtypes of CVD [16]. Another study conducted in Nepal also stated that smoking is known to increase the risk of heart artery disease in people in Nepal [17]. This result is in line with the study from Savia et al, (2013) which stated that there is a relationship between smoking and the risk of CVD.…”
Section: Discussionsupporting
confidence: 71%
“…Dalam penelitian Basnet et al, 2019 dikatakan bahwa pasien PJK cenderung memiliki IMT overweight ataupun normal. 18 Diketahui peningkatan IMT dalam tubuh dapat memicu terjadinya peningkatan trigliserida, hal ini mengakibatkan peningkatan hidrolisis pada lipase hati sehingga nantinya pembentukan HDL akan menurun. Selain itu, peningkatan IMT juga dapat menyebabkan terjadinya peningkatan dari leptin dan CETP yang dapat mempengaruhi kadar HDL dalam tubuh.…”
Section: Pembahasanunclassified